Decrease of endurance performance during Olympic Triathlon - de Vito, G.; Bernardi, M.; Sproviero, E.; Figura, F. (International Journal of Sports Medicine, 1995)
The present study was carried out in order to quantify the athlete's endurance impairment after two out of three sequential events of Olympic Triathlon (OT). Furthermore the significance of ventilatory threshold (Tvent) and peak of oxygen uptake (VO2peak) as triathlete's performance predictors was assessed. Tvent and VO2peak were measured in six male triathletes performing an incremental treadmill test a week before an ad hoc triathlon event. The same test was applied immediately after the first two segments of the triathlon (1.5 km swim, 32 km bike). VO2peak and Tvent measured during the latter test were reduced compared to the first test. VO2peak decreased from 69 to 64 ml.kg-1.min-1 and Tvent from 58 to 51 ml.kg-1.min-1 p < 0.01), respectively. VO2peak and Tvent measured in the first test were well correlated (P < 0.05) to both running and cycling times. The Tvent measured during the second test was related to the running time but with a higher significance (p < 0.01) than in the first test. The impairment in the endurance performance induced by the first two segments of OT is an important aspect to consider both in training and in race strategy. These results also provide evidence that VO2peak and Tvent are good predictors of triathlon performance at least in cycling and running events.